Tracking Users’ Clicks and Submits: Tradeoffs between User Experience and Data Loss - Kohavi, Ron; Messner, David; Eliot, Seth; Lavista Ferres, Juan M.; Henne, Randy; Kannappan, Vignesh; Wang, Justin (2010)
Tracking users’ online clicks and form submits (e.g., searches) is critical for web analytics, controlled experiments, and business intelligence. Most sites use web beacons to track user actions, but waiting for the beacon to return on clicks and submits slows the next action (e.g., showing search results or the destination page). One possibility is to use a short timeout and common wisdom is that the more time given to the tracking mechanism (suspending the user action), the lower the data loss. Research from Amazon, Google, and Microsoft showed that small delays of a few hundreds of milliseconds have dramatic negative impact on revenue and user experience (Kohavi, et al., 2009 p. 173), yet we found that many websites allow long delays in order to collect click. For example, until March 2010, multiple Microsoft sites waited for click beacons to return with a 2-second timeout, introducing a delay of about 400msec on user clicks. To the best of our knowledge, this is the first published empirical study of the subject under a controlled environment. While we confirm the common wisdom about the tradeoff in general, a surprising result is that the tradeoff does not exist for the most common browser family, Microsoft Internet Explorer (IE), where no delay suffices. This finding has significant implications for tracking users since no waits is required to prevent data loss for IE browsers and it could significantly improve revenue and user experience. The recommendations here have been implemented by the MSN US home page and Hotmail.